Genetic diversity status of only registered cattle breed of Chhattisgarh-Kosali - SHARMA, HIMANI; SHARMA, REKHA; AHLAWAT, SONIKA; N, RAJA K; JAIN, ASIT; TANTIA, M S (The Indian Journal of Animal Sciences, 2020)
Assessment of diversity is essential for germplasm characterization and management. Kosali is the first and only registered breed of Chhattisgarh state which immensely contributes to the local economy of 70% farmers. Genomic microsatellite markers being valuable tool for estimating genetic diversity were selected for exploring existing genetic variability in Kosali cattle population. The standard metrics of genomic diversity detected high variability in this breed. All the loci were polymorphic resulting in 297 alleles. Mean values of observed and expected number of alleles were 11.423±0.877 and 4.989±0.372, respectively. Similarly, higher mean values of observed heterozygosity (0.693±0.031) also corroborated with the allelic diversity. Mean expected heterozygosity (0.765±0.02) under Hardy-Weinberg equilibrium (HWE) was higher than the observed values indicating some deviations from assumptions of the model. It can be attributed to the forces such as inbreeding. In fact a positive FIS value of 0.088±0.038 indicated some heterozygote deficiency in the population. Bottleneck analysis indicated that Kosali cattle have not suffered any population bottleneck event during evolutionary trajectory. This study is first to report the genetic diversity status of Kosali cattle based on microsatellite markers.The results imply the necessity of management programs in order to conserve the existing genetic variation and to avoid any escalation of inbreeding.